The productive Muslim : where faith meets productivity - Faris, Mohammed (Swansea, U.K. : Awakening Publications, 2016)
Ever wondered if there's a practical way to lead a productive lifestyle that combines the best of Islamic tradition and modern psychology and science? In'The Productive Muslim' Mohammed Faris, the founder of ProductiveMuslim.com, provides this practical framework that helps urban global Muslims lead a productive lifestyle--spiritually, physically, and socially.
Sumbangan Mohamad Taha (2017).
Keywords: Islam -- Personal development; Muslims -- Conduct of life; Muslims -- Life skills guides